Essays on renewable energy, emissions and policies - Shodipe, Oladimeji Tomiwa (My University, 2025)
This dissertation consists of three essays on renewable energy expansion, emissions, economic performance, policy frameworks, and macroeconomic shocks across U.S. states. The first chapter studies the impact of renewable energy generation on electricity prices and economic activities in the U.S. The second chapter explores the relationship between state-level energy efficiency policies, disclosure policies and emissions in the U.S. The third chapter examines the impact of monetary shocks on the variations in renewable energy capacities. The first essay examines renewable energy generation and the economic and price impacts across U.S. states. Given the wide variation in renewable energy expansion and efficiency performance, the chapter employs the American Council for an Energy-Efficiency Economy (ACEEE) Scorecard and state-level political and policy indicators to classify states according to their renewable adoption and efficiency programs. Using a heteroscedasticity-identified structural vector autoregression (SVAR), the analysis finds that states in the upper developmental stage of renewable energy benefit more economically from renewable investments, experiencing increased economic activity and reduced electricity prices. States where renewables compete with conventional sources exhibit stronger responses. The findings in this study underscore the need for continued investment in clean energy technologies. The second essay investigates the effects of state-level energy efficiency policies, disclosure mandates, and political orientation on greenhouse gas (GHG) emissions between election cycles. This chapter finds that states adopting energy disclosure policies achieved significant emissions reductions in Democrat-led states. Energy efficiency improvements in the transportation sector emerged as the only statistically significant factor driving GHG reductions among all the five policy areas considered in this study. These findings highlight the importance of targeted efficiency programs in emissions reductions. The third essay analyses the impact of unanticipated monetary policy shocks on renewable energy capacity. While previous studies have investigated the effects of monetary shocks using various instruments, this chapter offers a novel perspective by examining the influence of treasury-based measures. The empirical results show that monetary shocks statistically cause changes in renewable energy capacities. Disaggregated analysis reveals that monetary shocks significantly influence hydroelectric and bio-energy capacities, while wind and solar remain largely unresponsive to monetary shocks. These findings suggest that renewable infrastructure is not immune to broader economic fluctuations.
Keywords: Renewable energy; Electricity price; Greenhouse gas emissions; Energy efficiency; Monetary policy; Economic activities